Isothermal Kinetics of Diesel Soot Oxidation over La0.7K0.3ZnOy Catalysts - Ram Prasad; Abhishek Kumar; Anupama Mishra (Bulletin of Chemical Reaction Engineering & Catalysis, 2014)
This paper describes the kinetics of catalytic oxidation of diesel soot with air under isothermal conditions (320-350 oC). Isothermal kinetics data were collected in a mini-semi-batch reactor. Experiments were performed over the best selected catalyst composition La0.7K0.3ZnOy prepared by sol-gel method. Characterization of the catalyst by XRD and FTIR confirmed that La1-xKxZnOy did not exhibit perovskite phase but formed mixed metal oxides. 110 mg of the catalyst-soot mixture in tight contact (10:1 ratio) was taken in order to determine the kinetic model, activation energy and Arrhenius constant of the oxidation reaction under the high air flow rate assuming pseudo first order reaction. The activation energy and Arrhenius constant were found to be 138 kJ/mol and 6.46x1010 min-1, respectively. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)